Efeito de um programa de exercício físico em ambiente domiciliar no espaço de vida de idosos com Alzheimer: ensaio clínico cego controlado e randomizado - Barreiros, Bruna Anzolin (Universidade Federal de São Carlos, 2021)
Introduction: Alzheimer's disease (AD) has a slow and progressive evolution, with a degenerative and disabling character. The decline in mobility is one of the factors that stands out in the course of the disease. Regular physical exercise has been shown to be an important component in the treatment of older adults with AD. However, the effect of exercise on life space mobility (LSM) in this population has not yet been explored. Objective: to evaluate the effect of the physical exercise program in the home environment on life space mobility of older adults with AD; to evaluate the effects of the physical exercise program in the home environment on physical capacity, functionality, functional capacity and the level of physical activity. Methods: Controlled, randomized, blinded clinical trial conducted with older adults (≥ 65 years old) diagnosed with mild and moderate AD, divided into an intervention group (IG) and a control group (CG). The following evaluations were applied: Addenbrooke's Cognitive Exam (ACE-R), Life Space Assessment (LSA), World Health Organization Disability Assessment Schedule (WHODAS), Modified Baecke Questionnaire for the Older people (MBQOP), Timed Up and Go Test (TUG); Short Physical Performance Battery (SPPB); Activities of Daily Living Questonnaire (ADLQ), Environmental Assessment Guide and Environmental Perception Scale for Physical Activity (EPSPA). A physical exercise program was carried out in the home environment, developed to assist elderly people with AD, three times a week for 16 weeks. The CG was instructed to maintain health care and usual activities. Results: The home-based exercise program was not enough to contain the reduction in the life space mobility of older adults with AD, when considering the level of displacement, frequency, and need for assistance. However, when analyzing the need for assistance, it is noteworthy that for the maintenance of mobility in the neighborhood, the CG needed doubled the personal assistance after 16 weeks (21% to 42%), which did not occur in the group that received intervention. The exercise program did not alter physical capacity, functionality, or the level of physical activity. Conclusion: the home-based exercise program did not change the mobility of the life space mobility of older adults with mild and moderate AD.
Effect of a home-based physical exercise program on the life space of older adults with Alzheimer's: blinded randomized clinical trial
Keywords: Doença de Alzheimer; Espaço de vida; Mobilidade; Exercício físico; Fisioterapia; Alzheimer's disease; Life space; Mobility; Physical exercise; Physiotherapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE